Experiences and expectations of patients with obesity 3 months after metabolic and bariatric surgery: a qualitative study - Lu Chen; Haiyan Wang; Ling Deng; Nianxing Li; Yinyin Fan (BMJ Open)
Objectives Patients experience significant physical and psychological changes within the first 3 months post-surgery, yet few studies focus on patient experiences during the early postoperative period. This study aimed to explore the patient experiences and expectations for nursing follow-up during the home recovery period following metabolic and bariatric surgery.Design A qualitative descriptive study design was used. Participants were selected using a purposive sampling method, and semi-structured interviews were conducted to collect data, which then were analysed using the content analysis method.Setting The study was conducted in a tertiary hospital in eastern China.Participants 21 patients (8 men and 13 women; aged 18–51 years) who received metabolic and bariatric surgery were included, with 16 within 3 months post-surgery and 5 beyond 3 months.Results Four themes emerged: (1) Physical and psychological rehabilitation: patients were enthusiastic and motivated about their physical recovery and mental well-being. (2) Stress and challenges: patients encountered various pressures and challenges, especially in dietary transitions and emotional management. (3) Adjustment and adaptation: patients were committed to managing discomfort and developing healthy dieting strategies through personal effort and diverse support. (4) Expectations for comprehensive support: patients desire comprehensive support and services from healthcare providers.Conclusions Healthcare providers should focus on the early postoperative experiences of patients and deliver personalised health education and emotional support to help them navigate the postoperative adaptation and ultimately achieve long-term health goals.